The State of the Economy at Graduation, Wages, and Catch-up Paths: Evidence from Switzerland - Elena Shvartsman (Institute of Labor Economics (IZA), 2018)
This paper analyses whether the short- and mid-term labour market outcomes of Swiss university graduates are affected by the state of the domestic economy at the time of labour market entry, where the economic conditions are captured by the regional unemployment rate at the time of graduation. This analysis contributes to the question as to whether labour market outcomes are determined inter alia by luck even under fairly stable labour market conditions. The study provides empirical evidence demonstrating that less favourable economic conditions at the time of labour market entry have a negative impact on the individuals' wages one year after graduation. However, there appears to be a partial catchup towards luckier cohorts in the subsequent four years, which is primarily explained by higher job mobility with respect to the number of jobs an individual has held since his graduation as well as tenure with the first job. Finally, there is strong evidence in favour of heterogeneous effects with respect to, for instance, individuals employed in part-time, for whom the negative effects appear to be most pronounced, while at the same time it is found that the probability of part-time employment rises under less favourable entry conditions.
Keywords: J31; J39; 330; labour market entry conditions; wages; job mobility